115k views
2 votes
Select the correct answer.

What is the solution for p in the equation?

1/3p + 1/2p = 7/6p +5 + 4

A.
p = -6
B.
p = -1
C.
p = 1
D.
p = 6

User QGA
by
4.9k points

2 Answers

2 votes

Final answer:

To solve for p in the equation 1/3p + 1/2p = 7/6p + 5 + 4, you need to combine like terms and isolate p. The solution is p = 27.

Step-by-step explanation:

To solve for p in the equation 1/3p + 1/2p = 7/6p + 5 + 4, you need to combine like terms and isolate p on one side of the equation.

Multiply the fractions by their respective denominators to eliminate the fractions. This gives us 2/6p + 3/6p = 7/6p + 9.

Combine like terms. On the left side, 2/6p + 3/6p = 5/6p. On the right side, 7/6p + 9 remains unchanged.

Subtract 5/6p from both sides to isolate p. This gives us 7/6p - 5/6p = 9.

Combine like terms on the left side. 7/6p - 5/6p = 2/6p.

Simplify the equation further. 2/6p = 9 can be reduced to 1/3p = 9.

Multiply both sides of the equation by the reciprocal of 1/3, which is 3/1. This gives us p = 9 * (3/1) = 27.

Therefore, the solution for p in the equation is p = 27.

User Silvan Bregy
by
4.8k points
0 votes

Answer:

Step-by-step explanation:

Problems such as this one become easier to solve if we first eliminate fractions. Here the LCD is 6 (which is 2 times 3).

Multiplying all 5 terms by 6, we get:

2p + 3p = 7p + 54, or

5p = 7p + 54. Then,

-2p = 54, or p = -27

Double check to ensure that you have copied down the last two terms (5 and 4) correctly.

User Andrey Baryshnikov
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.